Development and Validation of Extracorporeal Membrane Oxygenation Mortality-Risk Models for Congenital Diaphragmatic Hernia. Issue 6 (November 2018) - Guner, Yigit S.; Nguyen, Danh V.; Zhang, Lishi; Chen, Yanjun; Harting, Matthew T.; Rycus, Peter; Barbaro, Ryan; Di Nardo, Matteo; Brogan, Thomas V.; Cleary, John P.; Yu, Peter T.
Abstract : The purpose of our study was to develop and validate extracorporeal membrane oxygenation (ECMO)–specific mortality risk models for congenital diaphragmatic hernia (CDH). We utilized the data from the Extracorporeal Life Support Organization Registry (2000–2015). Prediction models were developed using multivariable logistic regression. We identified 4, 374 neonates with CDH with an overall mortality of 52%. Predictive discrimination ( C statistic) for pre-ECMO mortality model was C = 0.65 (95% confidence interval, 0.62–0.68). Within the highest risk group, based on the pre-ECMO risk score, mortality was 87% and 75% in the training and validation data sets, respectively. The pre-ECMO risk score included pre-ECMO ventilator settings, pH, prior diaphragmatic hernia repair, critical congenital heart disease, perinatal infection, and demographics. For the on-ECMO model, mortality prediction improved substantially: C = 0.73 (95% confidence interval, 0.71–0.76) with the addition of on-ECMO–associated complications. Within the highest risk group, defined by the on-ECMO risk score, mortality was 90% and 86% in the training and validation data sets, respectively. Mortality among neonates with CDH needing ECMO can be reliably predicted with validated clinical variables identified in this study. ECMO-specific mortality prediction tools can allow risk stratification to be used in research and quality improvement efforts, as well as with caution for individual case management.